The UKCTOCS Experience—Reasons for Hope?. (1st May 2012) - Menon, Usha; Kalsi, Jatinderpal; Jacobs, Ian
Abstract : Abstract: There has been concern about current ovarian cancer screening strategies after the publication showing a lack of benefit from screening in the ovarian part of the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial. The ongoing United Kingdom Collaborative Trial of Ovarian Cancer Screening involves 202, 638 low-risk postmenopausal women. The performance characteristics on prevalence screen in sensitivity, specificity, and stage distribution have been encouraging. Screening differs from the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial in the use of algorithms to interpret CA125 and ultrasound imaging and well-defined, centrally coordinated management of screen-detected abnormalities with protocols for intervention based on screening findings. There is a possibility that these essential differences may be sufficient to alter the natural history of ovarian cancer and ultimately lead to demonstration of a mortality benefit from screening when the trial reports in 2014/2015.